2023
DOI: 10.3389/fanim.2023.1147081
|View full text |Cite
|
Sign up to set email alerts
|

The importance of essential fatty acids and their ratios in aquafeeds to enhance salmonid production, welfare, and human health

Abstract: Long chain polyunsaturated fatty acids (LC-PUFA), namely those from omega-3 (n-3) and omega-6 (n-6) families, are paramount for both fish and human nutrition. Some of these biomolecules cannot be synthesized de novo and must be acquired through the diet, being termed dietary essential fatty acids (EFA). Fish requirements for EFA have traditionally been met through the incorporation of fish oil (FO) in the formulation of aquafeeds. However, with limited supply of FO the aquaculture industry is searching for add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Fish ingest these oils, which subsequently accumulate and enter our food chain. For their typical development, marine finfish necessitate Essential Fatty Acids (EFA), including n-3 High Unsaturated Fatty Acids (HUFA) like Docosahexaenoic Acid (DHA) and Eicosapentaenoic Acid (EPA) (Carr et al 2023). As a migratory species, tuna expands its nomadism as it reaches maturity, necessitating substantial fat deposition for energy storage.…”
Section: Discussionmentioning
confidence: 99%
“…Fish ingest these oils, which subsequently accumulate and enter our food chain. For their typical development, marine finfish necessitate Essential Fatty Acids (EFA), including n-3 High Unsaturated Fatty Acids (HUFA) like Docosahexaenoic Acid (DHA) and Eicosapentaenoic Acid (EPA) (Carr et al 2023). As a migratory species, tuna expands its nomadism as it reaches maturity, necessitating substantial fat deposition for energy storage.…”
Section: Discussionmentioning
confidence: 99%
“…34 Additionally, EPA and DHA also hold importance in promoting optimal fish growth and reproduction. [35][36][37][38] Utilizing offal from freshwater fish aquaculture as a supplement in fish diets could be a feasible alternative. 39,40 Moreover, the group size of fish exhibits lower levels of omega-3 fatty acids compared to omega-6 and omega-9 fatty acids (as indicated in Table 2).…”
Section: Fatty Acid Profiles Of Pangasius Catfish Groupsmentioning
confidence: 99%
“…The added value of AO on providing high levels of EPA + DHA, as well as on maintaining the ratio of these omega-3 EFAs (the optimum omega nutrition concept), includes better health and welfare and better fillet quality, which has been extensively documented for Atlantic salmon in scientific lab-scale trials (Santigosa et al, 2018(Santigosa et al, , 2020(Santigosa et al, , 2023. Fillet quality has further repercussions in human health because Atlantic salmon is considered the most valuable source of EPA and DHA for humans (Horn et al, 2019;Carr et al, 2023;Santigosa et al, 2023) and low EPA+DHA levels lead to low fish fillet quality (Oliva-Teles et al, 2015). Indeed, recent studies have shown that the EPA + DHA levels of commercialized Atlantic salmon fillets have been reduced by more than half in recent decades (Sprague et al, 2016(Sprague et al, , 2020.…”
mentioning
confidence: 99%